The effect of manganese on the olfactory bulb of adult male albino rat and the role of meloxicam: A histological and immunohistochemical study. Issue 1 (March 2015) - Mousa, Amany M.; Shehab, Amal A.
Abstract: Manganese (Mn) is an essential metal commonly found in the environment and is used for industrial purposes. Exposure to excessively high Mn levels may induce neurotoxicity referred to as manganism. This work was conducted to study the effect of manganese on the olfactory bulb of adult male albino rat and the possible protective role of meloxicam. Forty adult male albino rats were equally divided into four groups: control group, meloxicam-treated group (5 mg/kg/day orally for 4 weeks), MnCl2 -treated group (10 mg/kg/day orally for 4 weeks), and the fourth group received both meloxicam and MnCl2 at the same doses and duration. Specimens of the olfactory bulbs were prepared for light and electron microscopy. An immunohistochemical study with a quantitative morphometry was performed using antibodies against glial fibrillary acidic protein (GFAP). The control group and meloxicam-treated group showed the same normal structure. MnCl2 -treated group showed shrinkage of mitral nerve cells with dark peripheral nuclei as well as disorganization of mitral and granule nerve cells. The surrounding neuropil showed vacuolar spaces. Ultrastructurally, the mitral cells showed accumulation of lysosomes, swelling of mitochondria and irregularity of the nuclei. The nerve fibers contained swollen mitochondria with splitting and irregularity of the surrounding myelin sheaths. GFAP immunoreaction showed a highly significant increase compared to control group. On the other hand, the group that received both meloxicam and MnCl2 showed less marked histological changes. It was concluded that manganese induced structural changes in the olfactory bulb of albino rat that were ameliorated by concomitant use of meloxicam.